As dificuldades no processo de ensino e aprendizagem de trigonometria no ensino médio - OLIVEIRA, Francinete Pinheiro de (2022)
This paper presents a study that aimed to analyze the factors that contribute to the difficulties in the teaching and learning process of trigonometry in the 1st year of high school. As theoretical support, it was based on authors who discuss this theme as Brown (2006), Chigonga (2016), Orhun (2004), among others, who contributed with a meaningful approach to the topic under discussion. Thus, a qualitative research was carried out, in which observations and questionnaires were applied to a teacher and students of a class of the first year of high school. Having through the questionnaires satisfactory results regarding the difficulties that students have in learning Trigonometry, which concludes from this discussion show that the introduction of new methodological strategies for teaching aims to increase the educational potential in student learning. regarding trigonometric knowledge, as well as the other subjects of the school curriculum.